Front Cover: Revealing Phosphorus Nitrides up to the Megabar Regime: Synthesis of α′‐P3N5, δ‐P3N5 and PN2 (Chem. Eur. J. 62/2022). Issue 62 (26th October 2022) - Laniel, Dominique; Trybel, Florian; Néri, Adrien; Yin, Yuqing; Aslandukov, Andrey; Fedotenko, Timofey; Khandarkhaeva, Saiana; Tasnádi, Ferenc; Chariton, Stella; Giacobbe, Carlotta; Bright, Eleanor Lawrence; Hanfland, Michael; et al.
Abstract : For the last 30 years, the lack of a binary phosphorus nitride containing PN6 octahedra formed a scientific chasm between carbon‐group and oxygen‐group nitrides, both featuring a variety of solids with XN6 units (X being a non‐metal element). Now, the discovery of the δ‐P3 N5 and PN2 phosphorus nitrides—formed under high pressure and both composed of the elusive PN6 octahedron—builds a long‐sought‐after bridge between these two groups of nitrides. More information can be found in the Research Article by D. Laniel, F. Trybel, and co‐workers (DOI: 10.1002/chem.202201998 ).